Pemberian minyak pala (Myristica fragrans) Houttuyn 1774 sebagai bahan anestesi dengan konsentrasi berbeda pada benih lobster air tawar (Cherax quadricarinatus) Von Martens 1868 - Mamuko, Nelsi; Mingkid, Winda M.; Watung, Juliaan Ch.; Kreckhoff, Reni L.; Longdong, Sammy N. J.; Manginsela, Fransine B. (e-Journal BUDIDAYA PERAIRAN, 2022)
This study aimed to examine the best concentration of nutmeg oil for anesthesia of freshwater crayfish (Cherax quadricarinatus) seeds and analyze the length of time to faint, the length of time to faint and the length of time to wake up for the seeds of freshwater crayfish (C. quadricarinatus) . This research was carried out at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Sciences, Sam Ratulangi University, Manado. The time of the research was carried out from April 18, 2021 - May 18, 2021. This study used a completely randomized design (CRD) consisting of 5 treatments and 3 replications, thus there were 15 experimental units. Treatment A with a dose of nutmeg oil (0.7 mL), treatment B (1 ml), treatment C (1.3 mL), treatment D (1.6 mL) and treatment E (1.9 mL). Parameters observed during behavioral research, length of time to faint, length of time to faint and length of time to wake up. The results of the study using the ANOVA statistical analysis test and the BNT follow-up test (Least Significant Difference) showed that different doses of nutmeg oil had a very significant effect on the length of time to faint, the length of time to faint and the length of time to wake up. The length of time to pass out the fastest, the longest length of time unconscious and conscious longest duration was obtained in treatment E (1.9 mL).